Synthesis of novel nanocomposites reinforced with 3D graphene/highly-dispersible nanodiamonds nano-hybrids. Issue 10 (July 2019) - Liu, Chunlei; Zang, Jianbing; Yan, Shuang; Yuan, Yungang; Xu, Hanqing; Yang, Guoping; Wang, Yanhui
Abstract: The phenolic resin-based ternary nanocomposites were prepared successfully by filling a three-dimensional (3D) graphene network structure embedded with highly-dispersible nanodiamonds into the resin matrix. Firstly, 3D graphene/nanodiamonds hydrogels were fabricated via self-assembly approach in a self-made dispersing medium, in which the volume ratio of ethanol absolute to deionized water was equal to 1:1. Then water molecules within the as-prepared hydrogels were replaced with resol by means of soaking and appropriate heat treatment. In-situ polymerization technique was employed subsequently to afford the ternary nanocomposites of phenolic resin/3D graphene/nanodiamonds, while the dispersion of nanodiamonds remained decent. The obtained nanocomposites exhibited high hardness and compressive strength, where the measured values were 31.1% and 24.7% higher than that of the composites procured from direct dispersion of nanodiamonds in phenolic resin matrix, respectively.